Positivity of Carbapenemase-producing Enterobacteriaceae in Patients Following Exposure within Long-term Care Facilities in Seoul, Korea - Park, Jin Ju (J Korean Med Sci, 2020)
BACKGROUND: Carbapenemase-producing Enterobacteriaceae (CPE) are emerging as a worldwide threat. Long-term care facilities (LTCFs) are considered a reservoir for CPE and play a central role in transmission to acute care hospitals. We investigated the CPE positivity in patients exposed to CPE in LTCFs. Furthermore, we analyzed the CPE positivity rates in the environment exposed to CPE. METHODS: We collected rectal swab specimens from patients residing in LTCFs who were exposed to CPE. Environmental sampling was performed by infection control practitioners from sites classified as patient private space, common space in the patient room, common space other than patient rooms, and nursing station. Each sample was cultured on a Chrom Klebsiella pneumoniae carbapenemase (KPC) agar for CPE screening. The positive isolates were subjected to a polymerase chain reaction to identify the presence of bla(KPC), bla(VIM), bla(IMP), bla(OXA-48), and bla(NDM) and determine CPE genotype. RESULTS: From 65 index cases, a total of 24 hospitals and 481 patients were enrolled; 414 patients who had resided in the same patient room as a patient with confirmed CPE and 67 patients who were newly admitted to that patient room. A total of 117 (24.3%) patients were positive for CPE among which 93 (22.5%, 93/414) were already admitted patients and 24 (35.8%, 24/67) were newly admitted patients. A total of 163 CPEs were detected and K. pneumoniae (n = 104, 63.8%) was the most common bacteria followed by Escherichia coli (n = 43, 26.4%) and Citrobacter koseri (n = 11, 6.7%). Environmental sampling was performed in 24 hospitals and 604 sites. A total of 12 sites (2.0%) were positive for CPE and sink in the nursing station (n = 6, 4.2%) was the most contaminated space. CONCLUSION: CPE colonization rates in patients exposed to CPE in LTCFs were higher than those found in acute care hospitals. Proper infection control measures for detecting and reducing CPE colonization in patients residing in LTCFs are required. Newly admitted patients could also be carriers; therefore, infection control for newly admitted patients also needs to be thorough.